WHERE IS OUR HOME? - van de Beek, B (Acta Theologica, 2018)
Early Christians considered themselves strangers in the world. This view was deeply rooted in the forgoing Jewish tradition. The Torah begins with human beings who are not at home; they had been driven away from the garden of Eden. The patriarchs dwelled as sojourners in Canaan. Later, Israel ended with the diaspora. According to the New Testament, Christians are strangers even more, because their home is in heaven with Christ. Consequently, they can be at home everywhere, since they are at home nowhere. Therefore, nationalism or striving for an ideal society should be alien to Christians. They only support the well-being of the country in which they live, as far as that is possible in a world where human beings are never really at home – a situation of which Christians are fully aware. It is precisely by this attitude that they contribute most to the well-being of other people.